PROSPEK AMANDEMEN UNDANG-UNDANG DASAR NEGARA RI TAHUN 1945 TERKAIT MASA JABATAN PRESIDEN PERSPEKTIF PADA PEMILU 2024 - Roza, Darmini (Universitas Ekasakti, 2021)
The prospect of amendments carried out by a country shows that the country is following developments that the present will certainly not be the same in the future. Indonesia, which has undergone the replacement of the Constitution and the Amendment to the Law, has appointed Indonesia as a country to be better than in the past. Article 37 of the 1945 Constitution of the Republic of Indonesia becomes the Fundamental Basis. Related to legal issues and discourses on the terms of office of the President and Vice President for three periods which have led to polemics for and against, however, if it is related to the opportunities that exist in the MPR as a State Institution, amend Article 7 of the Constitution regarding the terms of office of the President and Vice President and fulfill the provisions of Article 37 of the Law. The Constitution and the people's approval so that the past history in this country does not repeat itself, meaning that it is normatively legal for the 2024 Election.